2020
DOI: 10.1177/1049731520908326
|View full text |Cite
|
Sign up to set email alerts
|

The Early Implementation of FFT-CW®, MST-Psychiatric®, and SafeCare® in Australia

Abstract: Purpose: In 2017–2018, the state of Victoria, Australia, initiated the implementation of five family and parenting programs within family services. Three—SafeCare®, Functional Family Therapy-Child Welfare®, and Multisystemic Therapy-Psychiatric®—originated in the United States and were supported through overseas intermediary or purveyor organizations (IPOs). This study examines the challenges and barriers faced by service agencies and their staff during the initial implementation of these three research-suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…The findings from this survey showed that these organizations used a range of 32 distinct implementation strategies across five domains, indicating a greater breadth of strategy use than identified through this review. This breadth was later confirmed as part of a program evaluation, reporting that intermediaries used 31 strategies in supporting the early implementation of three different manualized RSIs in Australia (Albers, Hateley-Browne, et al, 2020). One explanation for this difference may be the underreporting of strategy use in the studies included in this review, a challenge commonly acknowledged in the literature (Bunger et al, 2017; Hooley et al, 2020; Pinnock et al, 2017b; Varsi et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
“…The findings from this survey showed that these organizations used a range of 32 distinct implementation strategies across five domains, indicating a greater breadth of strategy use than identified through this review. This breadth was later confirmed as part of a program evaluation, reporting that intermediaries used 31 strategies in supporting the early implementation of three different manualized RSIs in Australia (Albers, Hateley-Browne, et al, 2020). One explanation for this difference may be the underreporting of strategy use in the studies included in this review, a challenge commonly acknowledged in the literature (Bunger et al, 2017; Hooley et al, 2020; Pinnock et al, 2017b; Varsi et al, 2019).…”
Section: Discussionmentioning
confidence: 92%
“…To date, there has only been one published study employing CFIR in the child maltreatment field [ 4 ]. That study focused on the implementation of one of the programs examined in the current study (FFT-CW ® ) in another Australian state (Victoria).…”
Section: Discussionmentioning
confidence: 99%
“…The increased complexity of the methods required to evaluate these multi-level, complex programs means that the cost of designing and implementing evaluations has also increased [ 3 ]. Identifying the enablers of, and barriers to, the delivery of multi-level programs at an early stage of their implementation is especially important because it is a particularly volatile stage in the program delivery process [ 3 , 4 ]. Moreover, identifying the factors that influence the early implementation of a program creates the opportunity for the enablers to be leveraged and the barriers to be modified, to optimally tailor the program to the context in which it is being delivered before the processes that support its implementation become entrenched [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Without question, the international dissemination and implementation of SafeCare is no small undertaking. As noted by Albers et al ( 2020 ), the geographical distance from an overseas model purveyor amplifies implementation challenges. Even when well resourced, the implementation process can be fragile and tenuous.…”
Section: Safecare: a Retrospective Of Model Developmentmentioning
confidence: 99%